(untitled) (Fiep Bulletin - online, 2012)
The practice of physical activity has been present since the pre-Inca period. Proof of this are the severalmanifestations found in the various ceramics (huacos) of the Mochica, Nazca, Tiahuanaco Vicús cultures. Thesephysical activities were related to military water activities performed at sea. The writings of the Spanish conquest chroniclers make references to physical activities in the IncaEmpire, such as the Warachicuy, Inti Raymi, practice of ball games and the participation of Chasquis.